INFLUENCE OF POST-SHOOTING SPRAYS OF SULPHATE OF POTASH AND CERTAIN GROWTH REGULATORS ON BUNCH CHARACTERS AND FRUIT YIELD OF BANANA CV. NENDRAN (FRENCH PLANTAIN MUSA AAB) - JAGADEESHA MULAGUND, (The Bioscan, 2015)
An investigation was carried out in Banana cv. Nendran with aiming to improve the bunch and fruit yield characters. The investigation consist of post-shoot application of SOP (2 %) as a main plot treatment and growth regulators (50 ppm GA3, 25 ppm 2, 4-D, CPPU and Brassinostroid @ 2 ppm) as a subplot treatments under split plot design. The combined foliar sprays of 2 per cent SOP and 2 ppm Brassinosteroid significantly increased the bunch characters viz., bunch weight (11.35 kg), finger weight (215.40 g), finger length (29.10 cm), pulp weight (180.22 g), pulp to peel ratio (5.13) and total bunch yield (29.38 tonnes/ ha) with relatively higher benefit: cost ratio (2.87). Thus, the study clearly indicates that combined post-shoot application of SOP (2%) with 2 ppm Brassinosteroid improves the bunch characters and fruit yield with economically cost viable.